The History of Contemporary Italy 1943-2019 - Gentiloni Silveri, Umberto (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book offers a history of contemporary Italy from the collapse of Mussolini to the present, placing this major Euro-Mediterranean country in a wider geo-political perspective. It examines how Italian history and politics developed in relation to - and were shaped by - the international context, from the Cold War and NATO to the European integration process and the global challenges of 1989. Umberto Gentiloni Silveri highlights all major events, structural limits, contradictions and conflicts influencing Italian democracy and the political system until today. He explores the continuous tension between 'stabilization' and 'conflict', between the promise of an innovative and evolutionary representative democracy on the one hand and the constraints of a political system conditioned by structural limits and old contradictions on the other. Umberto Gentiloni Silveri is Full Professor of Contemporary History at Sapienza University of Rome, Italy.
1. Foreword -- 2. Postwar -- 3. The Economic Miracle -- 4. The Seventies -- 5. Funeral of a Republic -- 6. Toward the End -- 7. The Collapse -- 8. The Impossible Transition -- 9. Between Europe and the Mediterranean -- 10. Conclusion.
Keywords: History, Modern; Italy-History.; Social history; Civilization-History.; Modern History; History of Italy; Social History; Cultural History